An optimized b‐value distribution for triexponential intravoxel incoherent motion (IVIM) in the liver. Issue 4 (17th November 2020) - Riexinger, Andreas; Martin, Jan; Wetscherek, Andreas; Kuder, Tristan Anselm; Uder, Michael; Hensel, Bernhard; Laun, Frederik Bernd
Abstract : Purpose: To find an optimized b‐value distribution for reproducible triexponential intravoxel incoherent motion (IVIM) exams in the liver. Methods: A numeric optimization of b‐value distributions was performed using the triexponential IVIM equation and 27 different IVIM parameter sets. Starting with an initially optimized distribution of 6 b‐values, the number of b‐values was increased stepwise. Each new b‐value was chosen from a set of 64 predefined b‐values based on the computed summed relative mean error of the fitted triexponential IVIM parameters. This process was repeated for up to 100 b‐values. In simulations and in vivo measurements, optimized b‐value distributions were compared to 4 representative distributions found in literature. Results: The first 16 optimized b‐values were 0, 0.3, 0.3, 70, 200, 800, 70, 1, 3.5, 5, 70, 1.2, 6, 45, 1.5, and 60 in units of s/mm 2 . Low b‐values were much more frequent than high b‐values. The optimized b‐value distribution resulted in a higher fit stability compared to distributions used in literature in both, simulation and in vivo measurements. Using more than 6 b‐values, ideally 16 or more, increased the fit stability considerably. Conclusion: Using optimized b‐values, the fit uncertainty in triexponential IVIM can be largely reduced. Ideally, 16 or more b‐values should be acquired.